2013
DOI: 10.1155/2013/709865
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Wound Healing Potential ofResina Draconis (Dracaena cochinchinensis)in Animal Models

Abstract: Resina Draconis (RD) is a type of dragon's blood resin obtained from Dracaena cochinchinensis (Lour.) S.C. Chen (Yunnan, China). It has been used as a medicine since ancient times by many cultures. The ethanolic extract of Resina Draconis (RDEE) was evaluated for its wound-healing activity using excision and incision wound models in rats. Group I, the control group, was treated with ointment base. Group II, which served as a reference standard, was treated with moist exposed burn ointment (MEBO). Group III was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 29 publications
4
31
0
Order By: Relevance
“…Studies conducted on the phytochemical screening of P. biglobosa showed the presence of phytoconstituents such as anthraquinones, tannins, flavonoids, terpenes, saponins, phenols and steroids (Builders et al, 2016); these may be attributed to the wound healing activity of P. biglobosa. The enhanced wound healing activity of this extract could be related to a function of either the individual or the additive effects of the phytoconstituents which is similar to research conducted by Liu et al (2013). These bioactives have been reported to possess pharmacological properties such as antimicrobial, antioxidant, analgesic, and anti-inflammatory activities which promote the wound-healing process mainly due to wound contraction and increased rate of epithelization (Liu et al, 2013).…”
Section: Discussionsupporting
confidence: 58%
“…Studies conducted on the phytochemical screening of P. biglobosa showed the presence of phytoconstituents such as anthraquinones, tannins, flavonoids, terpenes, saponins, phenols and steroids (Builders et al, 2016); these may be attributed to the wound healing activity of P. biglobosa. The enhanced wound healing activity of this extract could be related to a function of either the individual or the additive effects of the phytoconstituents which is similar to research conducted by Liu et al (2013). These bioactives have been reported to possess pharmacological properties such as antimicrobial, antioxidant, analgesic, and anti-inflammatory activities which promote the wound-healing process mainly due to wound contraction and increased rate of epithelization (Liu et al, 2013).…”
Section: Discussionsupporting
confidence: 58%
“…Our findings that RD has encouraging therapeutic effects for pressure ulcers compared with other dressings are inline with those of an earlier meta‐analysis on therapeutic effect of TCM conducted by Qian . Similarly, in a pharmacological study evaluating the wound healing potential of RD, Liu reported a significant reduction in wound size and mean epithelization time as well as the higher expression of growth factors in the RD treated group. Regarding adverse effects, our finding is also in agreement with a toxicology study conducted by Zeng .…”
Section: Discussionmentioning
confidence: 82%
“…Modern pharmacological studies have found that RD contains a variety of active ingredients such as flavonoids, triterpenoids, glycosides, stilbenes, organic acids, phenols, and esters . It possesses hemostatic activity, some analgesic effect, vasoactive‐antithrombotic potency, immunomodulatory activity and wound‐healing properties . RD has been frequently used in China, with the effects of promoting blood circulation to remove blood stasis, relieving swelling and pain, and replenishing blood.…”
mentioning
confidence: 99%
“…Different complex processes such as inflammation, epithelialization, angiogenesis, granulation, tissue formation and the deposition of interstitial matrix are involved for tissue repair and wound healing. 44 Microorganisms, especially bacteria (S. aureus and P. aeruginosa) are responsible for inflammatory response in both acute and chronic wounds and delay the wound healing process. The aqueous fraction of MO leaves contains some phytochemical compounds such as alkaloids, triterpenoids, tannins, and flavonoids.…”
Section: Wound Healing Mechanism Of Moringa Oleifera Leaves Extractmentioning
confidence: 99%